IMPLEMENTASI PENDIDIKAN KECAKAPAN HIDUP (LIFE SKILLS) BERBASIS PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 22 PALEMBANG - Salamul’in; Abdul Roni; Supatmi; Suci Hartati (UNISAN JURNAL, 2022)
There are several problems that become the focus of research, namely: (1) how to implement life skills based on Islamic education?; (2) how are the efforts made in implementing life skills based on Islamic education?; (3) what are the obstacles in implementing life skills based on Islamic education? For this reason, in writing this thesis, the type of research used by the author is a qualitative descriptive research method, emphasizing the power of direct field observation and then analyzing data on existing data sources. And the results of this study indicate that Islamic education and life skills are components that cannot be separated, because they are a unified whole in relation to life. This study also shows that the concept of life skills can be used as a new direction of Islamic education, by integrating several aspects of life skills with Islamic education. From the results of this study, it can be concluded that the implementation of life skills can provide abilities, abilities and skills to students both in the field of information technology and religion. As a provision to live life, it is hoped that every student has the ability to personal, rational, social, academic and vocational skills that are integrated in Islamic education. And the results of this study indicate that Islamic education and life skills are components that cannot be separated, because they are a unified whole in relation to life. This study also shows that the concept of life skills can be used as a new direction of Islamic education, by integrating several aspects of life skills with Islamic education. From the results of this study, it can be concluded that the implementation of life skills can provide abilities, abilities and skills to students both in the field of information technology and religion. As a provision to live life, it is hoped that every student has the ability to personal, rational, social, academic and vocational skills that are integrated in Islamic education. The results of this study are expected to be used as a constructive vehicle in relation to improving the quality of Islamic education in the future, both theoretically and In practical terms, besides that the results of this study cannot be said to be final, therefore it is hoped that there will be further researchers who review the results of this study.